Access and use of WHO essential medicines in Italy - Petrella, Alessandro; Fortinguerra, Filomena; Cangini, Agnese; Pierantozzi, Andrea; Trotta, Francesco (Frontiers in Public Health, 2023)
Background: Many countries have used the WHO Essential Medicines List (EML) as a guide for health policy choices to promote efficient use of healthcare resources or have adopted the concept of essential medicines (EMs) to develop their own national medicines lists. The aim of this study was to analyse the availability and use in Italy of medicines included in the last updated 22 nd WHO EML.Methods: A comparison using ATC code (level 5 th ) was made between the medicines included in the WHO EML and those retrieved from the AIFA database. The availability (regulatory and reimbursement status) of EMs as well as the impact market share of EMs on in expenditure (million euros) and consumption (measured in DDDs) compared to overall of reimbursed medicines in 2021 were analysed.In 2021, about 85.2% (n=. 414) of medicines included in the WHO EML were commonly marketed in Italy; of these, 396 EMs were fully reimbursed by the Italian National Healthcare Service (INHS), corresponding to 81.5% (396/486) of the WHO EML, while the only remaining 18.5% (90/486) were either not authorized (n=72) or not reimbursed (n=18). The study found a low coverage for anti-parasitic, insecticides and repellent products (ATC P) and for genito-urinary system and sex hormones (ATC G). Even though medicines on Medicines belonging to the WHO EML, including the therapeutic alternatives, even if accounted about for approximately 48.5% of the expenditure for medicines reimbursed by INHS, they covered 74% of national drug consumption. Novel high-cost therapies indicated in both high prevalence diseases and rare conditions, mostly antineoplastic and immune-modulating agents (ATC L) not included in the WHO EML, were also guaranteed.In Italy a high coverage of EMs was found, being largely reimbursed by the INHS, also if when compared to other European countries. Essential medicines represented high percentage of the overall expenditure and consumption in Italy. The WHO EML could be an important tool to guide the health policy choices for high-income countries, although a more frequent update as well as a more easy access to information on rejected medicines are needed.